HUBUNGAN EXPLOSIVE POWER OTOT LENGAN BAHU DAN KOORDINASI MATA TANGAN DENGAN HASIL SHOOTING TEAM PUTRA BOLA BASKET PENDIDIKAN OLAHRAGA UNIVERSITAS RIAU - Risky hendra hendra; Slamet '; Kristi Agust Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The problem in this research while making observations on Physical Education team during a match in medicine cup, in previous years always get a champion but this year his performance declined, based on the observations of the authors in the complex game men's basketball team Riau University Sports Education pretty good but there are still many individual errors committed players, especially the ability to shoot the ball (shooting). The purpose of this study was to determine the relationship of explosive muscle power arm and hand eye coordination shoulder with the shooting men's basketball team Riau University Physical Education.The population in this study is the son team of Riau University of Physical Education, amounting to 12 people using the total engineering side where all the population sampled, to obtain research data used test Two-Hand Medicine Ball Put, throwing a tennis ball catching and shooting results, data were analyzed by simple and multiple product moment, then the data is processed with stasistic, to test for normality with lilifors test at significance level α = 0.05, the proposed hypothesis is explosive relationship shoulder and arm muscle power hand eye coordination with the shooting.Based on the data processed, it can be concluded kooefisien data correlation obtained a correlation of r = 0.87> rtabel = 0.602, it can be concluded Ho is rejected and Ha accepted, the relationship between the variables X1 and X2 to variable Y a significant relationship. Conclusion hypothesis is accepted with significance level α = 0.05, thus there is a significant relationship between the explosive power shoulder and arm muscles with hand eye coordination results son's basketball team shooting Physical Education University of Riau. Keywords: Explosive Power Muscle Arm Shoulder, Hand Eye Coordination, Results shooting